Підготовка спеціалістів в галузі транспортних технологій з використанням програмного забезпечення PTV VISION VISSIM - Таран, Ігор; Новицький, Олексій; Литвин, Вадим (Видавництво Львівської політехніки, 2015)
The modern specialists training might foresee the usage of progressive scientific and technical achievements, innovations and abilities to solve the current and strategic issues in multiple fields of nationaltechnological segment. In order to be in touch with new professional demands in the field of transport technologies the personnel must operate with high competence and new knowledge, skills and experience, especially while usage the multiple software.
Specialist training in the field of transport technologies using PTV VISSION VISSIM software